Fenologia, frutificação e propagação por estaquia da corticeira-da-serra (Erythrina falcata Benth.) - Betanin, Leonildo (2008)
The Brazilian coral, native species from Brazil, presents an elevated potential for ornamental use and rehabilitation of permanent preservation and degraded areas, but it has low capacity of natural renovation and difficulties forming seeds for the seedling production. The research has investigated , in 2005 and 2006, the blossoming and fructification of seven genotypes located in the region of the upper slopes in Northeastern Rio Grande do Sul, and the feasibility of the pollen grains of three of these genotypes. The stem propagation was also studied, as an alternative for seedling production, carried out in a greenhouse with intermittent nebulization, making use of carbonized rice shell (50%) + coconut fiber (50%) (v/v) as substrate. Stem herbacious and foliar cuttings were used (without leaves), collected in the spring and autumn, and the effect of the treatments with IBA (0, 1000, 2000 and 3000 mg L-1). The foliar cuttings (trifoliated) were prepared, in the first cutting, by removing the two lateral folioles and reducing the apical foliole by half and, in the second cutting, reducing the two lateral folioles by half, removing the apical foliole. The observations showed that the Brazilian coral presents variations between genotypes concerning the blossoming period, due to, possibly, the genetic variability and temperature conditions, even without the flowers emission in determined cycles. The average number was from 24 to 25,5 flowers per inflorescence. The elevated quantity of flowers that don t blossom and expose the reproductive organs (cleistogamy) make pollination difficult, no seeds were obtained from any of the genotypes. The percentage of feasible pollen grains differs between genotypes and inflorescences in the same plant. The feasibility of 70% to 97% of pollen grains show that this is not the restraint for the self-pollination and fructification. The stem cuttings presented elevated mortality and lack of rooting, with a bigger survival in the autumn, due to the lower temperatures. Foliar cuttings keeping two lateral folioles reduced by half, with IBA application, presented average rooting of 35,4%, but the lack of sproutings suggests the inexistence or impossibility to form vegetative germs capable of renovating a plant